2012
DOI: 10.1167/iovs.12-9604
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Medication and Incident Open-Angle Glaucoma

Abstract: Use of anticoagulants or platelet aggregation inhibitors appears not to be associated with incident OAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…This is in keeping with the results of a randomized, crossover trial of aspirin versus placebo 32 and also in agreement with results from the Rotterdam Study, which reported that use of anticoagulants or platelet aggregation inhibitors was not associated with incident open-angle glaucoma 33 . The Rotterdam Study did report a nonsignificant trend towards lower IOP in participants taking aspirin (−0.21 mmHg; 95% CI, −0.44 to 0.01), although this was not adjusted for concurrent oral β-blocker use 33 …”
Section: Discussionsupporting
confidence: 89%
“…This is in keeping with the results of a randomized, crossover trial of aspirin versus placebo 32 and also in agreement with results from the Rotterdam Study, which reported that use of anticoagulants or platelet aggregation inhibitors was not associated with incident open-angle glaucoma 33 . The Rotterdam Study did report a nonsignificant trend towards lower IOP in participants taking aspirin (−0.21 mmHg; 95% CI, −0.44 to 0.01), although this was not adjusted for concurrent oral β-blocker use 33 …”
Section: Discussionsupporting
confidence: 89%
“…Primary open-angle glaucoma (OAG) is a disease characterized by the irreversible loss of retinal ganglion cells, ultimately resulting in the loss of sight, 1 and it is a prevalent type of glaucoma in the Taiwanese population. 2 , 3 Statins act as selective inhibitors of HMG-CoA (3-hydroxy-3-methylglutaryl-coenzyme A) reductase and are widely used medications to lower cholesterol in patients with hyperlipidemia.…”
Section: Introductionmentioning
confidence: 99%
“…Transient myopia can also be caused by other drugs such as promethazine hydrochloride (Phenergan) [52], prochlorperazine (Compazine) [53], insulin [54][55][56][57], IGF1 and FGF2 [58], antithrombotic [59], opiate [60], tetracycline [15,61], aripiprazole [62,63], amisulpride [64], oseltamivir [65], mefenamic acid [66], ectasy [67], phendimetrazine and ephedrine used as anorexiants [68], equine antilymphocyte globulins [69], metronidazole [70], aspirine and deturgylone [71,72], isotretinoin (accutane) [3], isosorbide dinitrate [74], quinine [75].…”
mentioning
confidence: 99%